Gene Therapy Using Plasmid DNA Encoding Vascular Endothelial Growth Factor 164 and Fibroblast Growth Factor 2 Genes for the Treatment of Horse Tendinitis and Desmitis: Case Reports - Kovac, Milomir; Litvin, Yaroslav A.; Aliev, Ruslan O.; Zakirova, Elena Yu; Rutland, Catrin S.; Kiyasov, Andrey P.; Rizvanov, Albert A. (Frontiers in Veterinary Science, 2017)
In this clinical study, for the first time we used the direct gene therapy to restore severe injuries of the suspensory ligament branch and superficial digital flexor tendon in horses (Equus caballus). We injected the plasmid DNA encoding two therapeutic species-specific growth factors: vascular endothelial growth factor 164 and fibroblast growth factor 2 at the site of injury in the suspensory ligament branch and tendon. Treatment effects were evaluated with the use of clinical observation and ultrasound imaging during a period of a few months. We showed that gene therapy used within a period of 2–3 months after the injury resulted in the complete recovery of functions and full restoration of the severely damaged suspensory ligament and superficial digital flexor tendon.